Investigation of Oxy-Fuel Combustion through Reactor Network and Residence Time Data - Maria Angela Agizza; Ghobad Bagheri; Sebastian Bürkle; Tiziano Faravelli; Steven Wagner; Andreas Dreizler (Energies, 2021)
Oxy-fuel combustion is a promising strategy to minimize the environmental impact of combustion-based energy conversion. Simple and flexible tools are required to facilitate the successful integration of such strategies at the industrial level. This study couples measured residence time distribution with chemical reactor network analysis in a close-to-reality combustor. This provides detailed knowledge about the various mixing and reactive characteristics arising from the use of the two different oxidizing streams.